El turismo alternativo como clave para el desarrollo de la vereda de Buritaca (2021)
Tourism is an activity that every day takes more strength, because there are many reasons that lead a person to travel outside their usual environment, among them there is one that is gaining strength and is the connection of being with nature and with itself. Life in the city is becoming more and more stressful and routine; therefore, escaping to nature is tempting for travelers. This so-called typology of nature or alternative tourism (which includes ecotourism, adventure tourism and rural tourism) is a practice that is not only enriching for people, but also helps to control the carrying capacity in destinations and the preservation of nature. The present work is carried out from the need to create a guideline or strategic plan that helps the small villages or towns that enter the tourist activity to organize and promote it in a better way. As subject of study, the community of Buritaca, (rural area of Santa Marta, Colombia) is taken through a study with different approaches (qualitative and quantitative) that allows organizing the steps to follow and projects to implement in order to achieve tourism sustainable safe, sustainable and profitable.